Pengaruh Model Pembelajaran PBL Terhadap Aktivitas Belajar Dan Hasil Belajar Siswa Pada Materi Asam Basa - Wanti Dahlia Siregar; Lisnawaty Simatupang (Universitas Negeri Medan, 2020)
The objectives of this study is (1) to determine whether the learning activities of students who were taught with the Problem Based Learning model were higher than those of students who were taught using the Direct Instruction learning model (2) to determine whether the learning outcomes of students who were taught with the Problem Based Learning model is higher than the learning outcomes of students who are taught with the Direct Instruction learning model (3) to determine whether there is a correlation between student learning activities and student learning outcomes. The research instrument consisted of test instruments and non-test instruments. The analysis technique used is the right side test and correlation test or test (product moment). From the results of data analysis of learning outcomes obtained (1) student learning activities that were taught with the Problem Based Learning learning model (86,20) were higher than the learning activities of students who were taught with the Direct Instruction learning model (79,86) (2) learning outcomes students who are taught with the Problem Based Learning model (83.75) are higher than the learning outcomes of students who are taught with the Direct Instruction learning model (71.94) (3) there is a positive and significant correlation between student learning activities and student learning outcomes. taught by the Problem Based Learning model, the contribution of student learning activities to learning outcomes was 21.92% while 78.08% was caused by other factors.